Prior authorization delays biologic initiation and is associated with a risk of asthma exacerbations - Dudiak, Gregor J; Popyack, Jessica; Grimm, Christy; Tyson, Sara; Solic, John; Ishmael, Faoud T (Allergy and asthma proceedings, 2021)
Biologics are effective treatments for patients with severe allergic disease. Impacts of delays in the prior authorization process on clinical outcomes has not been studied. The objective was to quantify the times for approval and filling of biologics, and whether patients were at risk of exacerbations during this time frame. The times for insurance approval and pharmacy filling of biologics (omalizumab, benralizumab, mepolizumab, dupilumab) in 80 subjects with severe asthma (n = 60) or urticaria (n = 20) from our clinic were reviewed. We compared the impact of clinical features, insurance, specialty pharmacy on fill times, and quantified exacerbations and prednisone use while awaiting biologic initiation. The mean ± standard deviation (SD) time (days) from submission of a prescription to the first dose available for injection was 44.0 ± 23.2 days. This was composed of the mean ± SD time for insurance approval (21.5 ± 19.6 days) and the mean ± SD time for a specialty pharmacy to fill the medication (22.8 ± 14.1 days). There was no significant difference between the times for diagnosis (asthma versus urticaria), specific biologic, or insurance. The "buy and bill" system was faster than filling via a specialty pharmacy (mean ± SD, 7.3 ± 8.5 days versus 23.3 ± 21.3 days, respectively, p < 0.001). Clinical features of patients with fast versus slow approval times was not significantly different. The subjects with asthma were at high risk of exacerbations and need for prednisone while awaiting initiation of the biologics; 28 of 59 patients (47%) required prednisone, with an mean cumulative dose of 483.2 ± 273.7 mg per person. The prior authorization process for biologics was slow, and the subjects were at high risk of exacerbations during this time. The system needs to be improved to expedite approval and initiation of these medications.